2018
DOI: 10.1016/j.bbr.2017.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Positive reinforcement modulates fronto-limbic systems subserving emotional interference in adolescents

Abstract: Fronto-limbic systems play an important role in supporting resistance to emotional distraction to promote goal-directed behavior. Despite evidence that alterations in the functioning of these systems are implicated in developmental trajectories of psychopathology, most studies have been conducted in adults. This study examined the functioning of fronto-limbic systems subserving emotional interference in adolescents and whether differential reinforcement of correct responding can modulate these neural systems i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 85 publications
0
3
0
Order By: Relevance
“…This is in line with evidence from tasks assessing executive control in processes other than WM (e.g., dichotic listening tasks, modified Stroop tasks or spatial attention tasks; Schupp, Flaisch, Stockburger, & Junghöfer, 2006; Yiend, 2010). The literature on the impact of affective distractors on WM performance again is mixed, showing no effect (Jenness et al, 2018) or impaired behavioral (Ladouceur, Schlund, & Segreti, 2018; Stout, Shackman, Pedersen, Miskovich, & Larson, 2017; Tollenaar, Ruissen, Elzinga, & de Bruijn, 2017; Wingert, Blais, Ball, & Brewer, 2018) performance.…”
Section: Investigating the Impact Of Affective Properties On Wm In Thmentioning
confidence: 99%
“…This is in line with evidence from tasks assessing executive control in processes other than WM (e.g., dichotic listening tasks, modified Stroop tasks or spatial attention tasks; Schupp, Flaisch, Stockburger, & Junghöfer, 2006; Yiend, 2010). The literature on the impact of affective distractors on WM performance again is mixed, showing no effect (Jenness et al, 2018) or impaired behavioral (Ladouceur, Schlund, & Segreti, 2018; Stout, Shackman, Pedersen, Miskovich, & Larson, 2017; Tollenaar, Ruissen, Elzinga, & de Bruijn, 2017; Wingert, Blais, Ball, & Brewer, 2018) performance.…”
Section: Investigating the Impact Of Affective Properties On Wm In Thmentioning
confidence: 99%
“…On the other hand, some studies have demonstrated that the amygdala and amygdala pathways can predict the treatment outcome of social anxiety disorder and affect therapeutic effects ( Klumpp and Fitzgerald, 2018 ). Experimental evidence suggests that emotional stimuli can influence many different aspects of cognition and behavior, resulting in disrupted cognitive goals and less optimal task performance ( Vuilleumier et al, 2001 ; Ladouceur et al, 2018 ). Emotional processing and regulation interact with treatment in a number of diseases.…”
Section: Discussionmentioning
confidence: 99%
“…We proceeded to recruit a total of 39 Korean middle school students (female: 23; mean age: 13.53 years, SD: 0.25) with myopia. Sample size for the experiment was determined based on our prior study (Ryu et al, 2021 ) and on similar imaging studies with adolescents on attention research (White et al, 2016 ; Ladouceur et al, 2018 ; Shafer et al, 2020 ). Of the total recruited participants, eight participants had to be excluded due to repeated, excessive head movements (>3 mm, see below) during scanning.…”
Section: Methodsmentioning
confidence: 99%